2023
DOI: 10.1002/admi.202202518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Structure Defects on Thermal Transport at the Graphene–Water Interface

Abstract: The graphene microchannel heat sinks have attracted extensive attention due to its high cooling efficiency in microelectric devices. The interfacial thermal resistance (ITR) between graphene as the bottom layer of microchannel and water is one of the key factors of its good working performance. In this paper, the impacts of structure defects in graphene surfaces on ITR of the graphene–water interface are investigated using molecular dynamic simulations. The results indicate that graphene layer with different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…20,21 As a specific material, graphene has been investigated using the model of graphene−water interface with defects, and the graphene with different types of defects has been observed to effect the TBR. 22 For recent nano devices, understanding the interfacial thermal transport with single-atomic precision is crucial for further advancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 As a specific material, graphene has been investigated using the model of graphene−water interface with defects, and the graphene with different types of defects has been observed to effect the TBR. 22 For recent nano devices, understanding the interfacial thermal transport with single-atomic precision is crucial for further advancement.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, focusing on the vibrational properties of liquid–solid interfaces to understand the thermal transport mechanism, a previous study has shown that the structure of an adatom is the most effective for enhancing relatively low-frequency modes of the interface which dominate the thermal transport through the solid–liquid interface. Such a role of the single-atomic structures is essentially important for modulating vibrational properties at the surfaces. , As a specific material, graphene has been investigated using the model of graphene–water interface with defects, and the graphene with different types of defects has been observed to effect the TBR . For recent nano devices, understanding the interfacial thermal transport with single-atomic precision is crucial for further advancement.…”
Section: Introductionmentioning
confidence: 99%